2003
DOI: 10.1074/jbc.m211930200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Discontinuous Immunodominant Region Recognized by Human Anti-thyroperoxidase Autoantibodies in Autoimmune Thyroid Diseases

Abstract: The discontinuous immunodominant region (IDR) recognized by autoantibodies directed against the thyroperoxidase (TPO) molecule, a major autoantigen in autoimmune thyroid diseases, has not yet been completely localized. By using peptide phage-displayed technology, we identified three critical motifs, LXPEXD, QSYP, and EX(E/D)PPV, within selected mimotopes which interacted with the human recombinant anti-TPO autoantibody (aAb) T13, derived from an antibody phage-displayed library obtained from thyroid-infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 56 publications
1
50
1
4
Order By: Relevance
“…These regulatory proteins are expressed on NPA cell membrane and probably partially protect them from CDC. Combining the various human recombinants anti-TPO aAbs we selected by phage display and characterised in term of epitopes (Bresson et al, 2003(Bresson et al, , 2004Chapal et al, 2000;Rebuffat et al, 2006), could make it possible to improve complement activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These regulatory proteins are expressed on NPA cell membrane and probably partially protect them from CDC. Combining the various human recombinants anti-TPO aAbs we selected by phage display and characterised in term of epitopes (Bresson et al, 2003(Bresson et al, , 2004Chapal et al, 2000;Rebuffat et al, 2006), could make it possible to improve complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…Human recombinant anti-TPO scFv antibody B 4 was selected in our laboratory using a phage-display library and expressed as IgG 1 in baculovirus/insect cells system by Dr M Cerutti as previously described (Bresson et al, , 2003. Sera from patients suffering from Graves' disease were obtained from Dr B Guerrier (Guy de Chauliac Hospital, Montpellier, France) and Dr L Baldet (Lapeyronie University Hospital, Montpellier, France).…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cell proteins were extracted from CHO cells as previously described (12). Cell surface protein was isolated using the Cell Surface Protein Isolation Kit (Pierce) according to the protocol provided by the manufacturer.…”
Section: Total Cell Protein Isolation and Cell Surface Protein Biotinmentioning
confidence: 99%
“…These regions were firstly defined in competition experiments with a panel of murine monoclonal antibodies and patient autoantibodies (5), and subsequent studies with recombinant human anti-TPO Fab fragments confirmed these findings (6,7). Numerous attempts have been made to identify the amino acids in the autoantibodies' epitopes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); however, to clearly interpret these data and arbitrate between some conflicting results, the determination of the three-dimensional structure of TPO in complex with various autoantibodies is needed.…”
Section: Introductionmentioning
confidence: 99%